The Tendency of Bullying Behavior in SMP N 12 Padang and Implications for Guidance and Counseling Services - Mona Dianes; Alizamar Alizamar (Jurnal Neo Konseling, 2019)
Based on the phenomenon that researchers can be in the field when conducting interviews with several guidance and counseling teachers and students find that there are students who are perpetrators of bullying, students take acts of hazing, students take the act of "happy slapping", calling friends by name calls, take violent actions such as pinching, blackmailing and threatening. The purpose of this study is to describe (1) the tendency of bullying from the type of verbal bullying, (2) the tendency of bullying from the type of physical bullying, (3) the tendency of bullying from the type of relational bullying, and (4) the tendency of bullying from the type of cyberbullying behavior. This type of research is descriptive. The research subjects were 45 students of class VIII and IX of SMP N 12 Padang who were registered in the 2018/2019 school year. The instrument used in this study was a student bullying behavior questionnaire with a likert scale model. The data analysis technique used is the percentage technique. The research findings revealed that (1) the tendency of bullying behavior of students of SMP N 12 Padang seen from the type of verbal bullying was classified as high (2) the tendency of bullying behavior of students of SMP N 12 Padang viewed from its type. physical bullying is classified as moderate, (3) the tendency of bullying behavior of students of SMP N 12 Padang seen from the type of relational bullying is classified as high and (4) the tendency of bullying from the type of cyberbullying behavior is classified as moderate. . Based on these findings, it is expected that the guidance and counseling teacher helps students in minimizing the tendency of student bullying behavior by providing information services, content mastery services, group guidance services, group counseling services and individual counseling services with material related to student bullying behavior.